Critical Success factors of Strategic Information system and it's relation with Strategic Decisions Effectiveness - السامرائي, سلوى هاني (Journal of Economics and Administrative Sciences, 2012)
The organization uses many techniques and methods to ensure that they will succeed and adapted with velocity change in the internal and external environment by decision taking, especially strategic decisions.Strategic decisions are very important for organization success because it can predict the future and deal with uncertainty, in this circumstances they need accurate and comprehensive information to make effective strategic decision.To achieve that purpose it must owned successful Strategic Information System ( SIS ) and determined the critical success factors for this system ,which can assisted the worker to focus on the important activities to develop it.This research was tested the relation between Critical Success Factors of (SIS) and strategic decision effectiveness by questionnaire. The sample of research was (16) managers in the General Company for Vegetable Oil Industry.In the light of results ,the research attained to the number of conclusion, on of them the existence of significant positive correlation between the research's variables(critical success factors of ( SIS ) and strategic decision effectiveness).